"You're a great driver/Your driving scares me": Reactions of older drivers to family comments. (January 2019) - Caragata, Glenyth; Wister, Andrew; Mitchell, Barbara
Highlights: .Gender and driving habit moderate the influence of family statements on older drivers. Four statement domains were identified: continue, modify, reduce, and cease driving. Statements supporting elders to continue or reduce driving had the most influence. Abstract: Background and objectives: Age related changes often compromise the ability to drive safely. Some elders report that they listen to others' advice, but there have been no studies that have examined how much influence families have on their driving decisions. This study fills this gap by exploring older drivers' perceptions of how family members affect their driving decisions. Research design and methods: A quasi-experimental ranking task was used to examine the expected influence that 48 hypothetical statements, drawn from related literature, have on a convenience sample of 37 adults, age 70–96 years. Analysis was conducted by gender and by habit strength for driving. Results: Four domains of influence were identified from the literature, representing family aims to influence the elder to: (1) continue driving, (2) modify driving, (3) reduce driving, and (4) stop driving. Statements aimed at supporting the driver to continued driving (62%) and to reduce driving (62%) were found to have the most influence, with slightly less support for statements aimed to influence them to stop driving (58%) or modify their driving (52%). Women rated statements supporting them to continue driving as having the highest influence on them, whereas men reported that they were more influenced by statements encouraging them to reduce their driving. In addition, participants with high habit strength for driving were less likely to rate family statements as having a high influence on them. Discussion and implications: This study contributes new understanding of the influence of families on the driving decisions of older adults. These findings may be used to support families, in addition to informing the development of effective programs aimed at older driver safety.